Penggunaan Metode Moodie Young Pada Keseimbangan Lintasan Produksi Bola Lampu - Prasetyo, Didit Teguh; Sutrisno, Sutrisno; Siregar, Ninny (Universitas Medan Area, 2023)
The Use of Moodie Young Method in Balance of Light Bulb Production Line. Line production is a part of production activity which including set of working element works and working area. Several balance constraints on the production line are sometimes occurred in a company who runs in light bulb production, such as a bottleneck in the production process and accumulation of material at work stations due to the high idle times, also a gap in cycle time between the production times of each work station. The study employed the Moodie Young method by measuring three parts of balanced production line level, including Line Efficiency, Balance Delay, and Smoothness Index. The result pointed out that the actual production line values are Line Efficiency 43.69%, Balance Delay 56.30%, and Smoothness Index 703.64. The result also stated that there are improvement of the production line values by using Moodie Young method, which are values of Line Efficiency 76.46%, Balance Delay 23.53%, and Smoothness Index 279.39. To sum up, the high value of line efficiency and the low values of balance delay and smoothness index presents a good level of balanced the production line.